1995
DOI: 10.1002/ibd.3780010302
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Crohn's disease in end ileostomies

Abstract: : It appears well established that the recurrence rates following operations for Crohn's disease of ileum and colon are higher after anastomotic operations than after an end ileostomy. To obtain further information regarding the rate of recurrence following end ileostomy we reviewed the charts of 182 patients: 117 with involvement of the ileum as well as the colon, and 65 with Crohn's colitis only, who were operated upon at the Mt. Sinai Hospital during 1952-1984. They were followed until death or the first il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Of 2017 unique studies identified using our search strategy, 17 studies met our inclusion criteria . In addition, we identified one abstracts from conference proceedings and hence, included a total of 18 studies for quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 2017 unique studies identified using our search strategy, 17 studies met our inclusion criteria . In addition, we identified one abstracts from conference proceedings and hence, included a total of 18 studies for quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were performed in North America and 12 in Europe . Of note, three studies were performed at a single centre, of which two reported clinical recurrence over a non‐overlapping period, and one reported surgical recurrence; hence, all three studies contributed to the analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a group of 182 patients with an end ileostomy for CD 64% of those with ileocolitis as initial presentation had recurrence in the neoterminal ileum after 20 years, versus 15% of those with colitis (p < 0.001) (57).…”
Section: Surgery-related Factorsmentioning
confidence: 95%